Design of Web-Based E-Perpus Information System: Study at One MTS School in Cianjur - Asri Wasiatun Saadah; Rohmat Nur Ibrahim; Dheni Apriantsani Budiman (LPPM STMIK Mardira Indonesia, 2023)
The library of a specific MTS school in Cianjur currently employs a manual data processing system, which involves the utilization of handwritten notes in the form of notebooks. This research aims to transform the manual process of book data input and borrowing into a web-based digital medium utilizing object-oriented system development techniques and descriptive research methodologies. The application features a library menu that enables users to access a comprehensive list of available libraries remotely without needing a physical presence at the library. The software system has been developed utilizing the PHP programming language and MySQL database and is furnished with the Bootstrap framework. The findings of this investigation suggest that the utilization of computerized data processing procedures would facilitate ease of processing and yield outcomes of greater precision in contrast to manual methods.